Super-hydrophilic and high strength polymeric foam dressings of modified chitosan blends for topical wound delivery of chloramphenicol. (15th March 2019) - Michailidou, Georgia; Christodoulou, Evi; Nanaki, Stavroula; Barmpalexis, Panagiotis; Karavas, Evangelos; Vergkizi-Nikolakaki, Susan; Bikiaris, Dimitrios N.
Graphical abstract: Highlights: New chitosan grafted derivatives have been synthesized. Miscible blends of derivatives with chitosan have been prepared. The studied blends have super-hydrophilic and high strength properties. Blend dressings loaded with chloramphenicol offers a promising solution in wound infections. All dressing shows significant inhibition zone against bacteria strains. Abstract: In the present study polymer blends based on chitosan (CS) and its derivatives with trans-aconitic (t-Acon) acid and another with trimellitic (TRM) anhydride, were prepared for topical wound delivery of chloramphenicol (CHL). FT-IR spectroscopy revealed the successful grafting of t-Acon acid or TRM anhydride into CS macromolecules at molar ratios 1:1 and 1:0.5, while powder X-ray diffraction (XRD) analysis showed that the prepared materials were amorphous. Neat chitosan and its grafted derivatives were mixed in different ratios (25/75, 50/50 and 75/25 w/w) in order to prepare suitable blends. Scanning electron microscopy (SEM) showed that the formed blends after freeze-drying had a sponge-like structure, while thermogravimetric analysis (TGA) verified their thermal stability. All blends are miscible in studied compositions and have extensive swelling and much better mechanical properties than neat CS. In a further step, the obtained porous sponges prepared from CS/CS-derivatives 50/50 w/w were loaded with Chloramphenicol (10, 20 and 30 wt%), a broad-spectrum antibiotic, and the prepared dressings were evaluated in terms of FT-IR, XRD, SEM, and in vitro drug dissolution. An initial burst release followed by a quasi-Fickian diffusion driven sustained release phase was observed while the addition of chloramphenicol gives high antimicrobial properties to all dressings.